Effectiveness of Health Education on Fish Consumption Behavior in Populations at Risk of Coronary Heart Disease - Lilik Subagiyo Utomo; Beti Kristinawati (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Health education is important for people to know and want to prevent coronary heart disease by consuming fish. Fish is an animal that produces omega-3 to prevent coronary heart disease by reducing low-density lipoprotein, which causes plaque buildup on blood vessel walls. Coronary heart disease is caused by a blockage in the walls of blood vessels, preventing blood from reaching the heart. This research aims to increase public knowledge about fish consumption behaviour in populations at risk of coronary heart disease through health education in Nganjat Village, Polanharjo District, Klaten Regency. The research method used is quantitative research, using a Quasi Experiment type and research design with a